Pengaruh Flash Sale Effect terhadap Perceived Urgency Generasi Z Mahasiswa pada Shopee - Amanda Diva Nadia; Elis Pricillia; Melinda Maulinda; Ahmad Rendy Prasetyo; Ria Aulia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of flash sale effect on the perceived urgency of Generation Z consumers who are students at Universitas Pamulang on the Shopee e-commerce platform. A quantitative approach with an associative design was employed. Data were collected through structured questionnaires distributed to 46 respondents selected by purposive sampling. The independent variable is flash sale effect (X), while the dependent variable is perceived urgency (Y). Data analysis techniques include validity tests, reliability tests, normality tests, simple linear regression, Pearson correlation, coefficient of determination, and hypothesis testing (t-test). The results show that the mean flash sale effect score is 4.00 and the mean perceived urgency score is 3.97, both categorized as high. The regression equation obtained is Ŷ = 0.330 + 0.910X. The Pearson correlation coefficient of 0.859 indicates a very strong relationship between the two variables. The coefficient of determination (R²) of 0.738 reveals that 73.8% of the variance in perceived urgency is explained by flash sale effect. The t-test yields t-count of 11.142, exceeding t-table of 2.015 with a significance value of 0.000, confirming that the hypothesis of a positive and significant effect of flash sale effect on perceived urgency is accepted.